Analisis Kinerja Mesin Cane Unigrator dengan Penggerak Turbin Uap di PT. PG Rajawali II Unit Jatitujuh - NUGRAHA, FAHRUL AZIZ; Yunus, MT., Dr. H. Riza M. (SEMINAR TEKNOLOGI MAJALENGKA (STIMA), 2025)
Sugar production begins with the sugarcane milling stage at the milling station. The main machines at this station consist of sugarcane cutter, unigrator, and milling unit. The unigrator is powered by a steam turbine that converts steam energy into mechanical energy. This study aims to determine the production capacity of the unigrator within one hour. The results show that the unigrator requires 58.98 kW/Th of power with a Preparation Index (PI) of 91.728%. A higher PI value indicates better juice extraction performance. The unigrator requires 15.75 tons of steam per hour to operate optimally.